A lean production model to enhance operational efficiency in textile SMES: a case study - Mercado Seguil, Daniel (2025)
This research focuses on the application of a comprehensive lean production model to improve the root causes that cause the low efficiency rate within the sewing line of a textile SME. It can be confirmed that the implementation of this model allows to reduce the rate of reprocessed products, increase the delivery rate, improve the mean time between failures and decrease the average time between repairs; therefore, improve the efficiency in the production of the sewing line. In this case study, the Lean methodology was used to detect the root causes that produce the main problem of the work and Total Productive Maintenance (TPM), where what is known as preventive maintenance and the standardization of processes is applied to solve the root causes and that this continues to be carried out over time. The implementation was carried out in the sewing area of the company where results were achieved such as reducing the rate of reprocessed products from 15% to 2%, increasing the on-time delivery rate from 90% to 97%, increasing the average time between failures from 6.3 hours to 7.15 hours, reducing the average repair time from 1.3 hours to 0.75 hours and improving the efficiency rate from 55% to 75%.